A Multifaceted Study of Pseudomonas aeruginosa Shutdown by Virulent Podovirus LUZ19 - Lavigne, Rob (American Society of Microbiology, 2013)
In contrast to the rapidly increasing knowledge on genome content and diversity of bacterial viruses, insights in intracellular phage development and its impact on bacterial physiology are very limited. We present a multifaceted study combining quantitative PCR (qPCR), microarray, RNA-seq, and two-dimensional gel electrophoresis (2D-GE), to obtain a global overview of alterations in DNA, RNA, and protein content in Pseudomonas aeruginosa PAO1 cells upon infection with the strictly lytic phage LUZ19. Viral genome replication occurs in the second half of the phage infection cycle and coincides with degradation of the bacterial genome. At the RNA level, there is a sharp increase in viral mRNAs from 23 to 60% of all transcripts after 5 and 15 min of infection, respectively. Although microarray analysis revealed a complex pattern of bacterial up- and downregulated genes, the accumulation of viral mRNA clearly coincides with a general breakdown of abundant bacterial transcripts. Two-dimensional gel electrophoretic analyses shows no bacterial protein degradation during phage infection, and seven stress-related bacterial proteins appear. Moreover, the two most abundantly expressed early and late-early phage proteins, LUZ19 gene product 13 (Gp13) and Gp21, completely inhibit P. aeruginosa growth when expressed from a single-copy plasmid. Since Gp13 encodes a predicted GNAT acetyltransferase, this observation points at a crucial but yet unexplored level of posttranslational viral control during infection.